Progressive tumefactive fibroinflammatory lesion of the infratemporal fossa treated by radiation therapy - Hoebers, Frank J.P. (PAGEPress Publications, 2012)
Tumefactive fibroinflammatory lesion (TFIL) is a rare benign tumor in the head and neck region. We present a case of a 40-year-old female with a benign but progressive lesion of the infratemporal fossa, which was diagnosed as TFIL. Patient responded briefly to a course of steroid treatment but eventually showed progression and was unresponsive to further steroids. She was then treated with external beam radiation to a dose of 60 Gy in 30 fractions. After radiation a slow, gradual decrease in tumor size was noted over the course of years and she is free of disease after more than 11 years of follow-up. The major long-term side effect this patient developed was an expected unilateral radiation-induced retinopathy, due to the close proximity of the lesion to the orbit. The dilemma of treatment of benign disease with radiation with potential long-term complications is discussed and a review of the literature on TFIL is presented.